SOSIALISASI PERATURAN PEMERINTAH NOMOR 20 TAHUN 2026 PADA PT. SYINDO MULIA PERKASA - Nur Isra Laili (ASOSIASI IDEBAHASA KEPRI, 2026)
Government Regulation (PP) Number 20 of 2026 introduced significant changes to the eligibility criteria for Indonesia's 0.5% final income tax scheme, creating uncertainty among small business taxpayers regarding their tax obligations. This community service activity aimed to improve the understanding of the management of PT Syindo Mulia Perkasa, a single-shareholder limited liability company (Perseroan Perorangan), regarding the implications of the new regulation and its continued eligibility for the final income tax facility. The activity was conducted through preliminary needs assessment, regulatory socialization, case-based discussions, and interactive question-and-answer sessions involving the company owner and accounting staff. The results indicate that participants initially had limited knowledge of PP Number 20 of 2026 but, after the socialization, were able to correctly identify the applicable tax provisions, distinguish the tax treatment between Perseroan Perorangan and ordinary limited liability companies, and understand the conditions required to maintain eligibility for the 0.5% final income tax scheme. The activity successfully enhanced participants' awareness and reduced misconceptions regarding the implementation of the new regulation. These findings demonstrate that targeted regulatory socialization plays an important role in strengthening tax compliance and providing legal certainty for small business taxpayers..